2019
DOI: 10.1111/1759-7714.13058
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned from Linxian esophageal cancer etiological studies?

Abstract: Esophageal cancer is the sixth leading cause of cancer death in the world. Esophageal squamous cell carcinoma (ESCC) accounts for 90% of esophageal cancer cases, over half of which occur in China. Linxian, a county located in the North Central Taihang Mountain range, has the highest ESCC mortality rate, which may be the leading cause of death in this area. In a decades‐long research program in Linxian, Chinese and international scientists have exerted great efforts to describe the epidemiological characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…19,21,22 More than 90% of oesophageal cancer cases in this part of the world are of the squamous cell type (oesophageal squamous cell carcinoma). [22][23][24] However, tobacco and alcohol consumption, which are the major risk factors for oesophageal squamous cell carcinoma in many parts of the world, are not strong risk factors in the Asian oesophageal cancer belt. 22,23,25,26 Case-control and cohort studies have found that opium use, consumption of hot tea, low intake of fresh fruits and vegetables, indoor air pollution, exposure to polycyclic aromatic hydrocarbons, lack of access to piped water, poor oral health, and low socioeconomic status are also associated with a higher risk of oesophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…19,21,22 More than 90% of oesophageal cancer cases in this part of the world are of the squamous cell type (oesophageal squamous cell carcinoma). [22][23][24] However, tobacco and alcohol consumption, which are the major risk factors for oesophageal squamous cell carcinoma in many parts of the world, are not strong risk factors in the Asian oesophageal cancer belt. 22,23,25,26 Case-control and cohort studies have found that opium use, consumption of hot tea, low intake of fresh fruits and vegetables, indoor air pollution, exposure to polycyclic aromatic hydrocarbons, lack of access to piped water, poor oral health, and low socioeconomic status are also associated with a higher risk of oesophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…There are two types of EC, namely esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma. In China and other East Asian countries, up to 90% of cases are ESCCs (2). Shantou, in particular, is a high-risk area for ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…2 As is already known, the development of esophageal cancer is the result of the interaction of genes and environmental factors, but the specific pathogenesis of both have not as yet been fully elucidated, and need further exploration. 3 In recent years, studies have confirmed that gene single nucleotide polymorphism (SNP) was closely correlated with the cancer susceptibility. 4 Murine double minute 2 (MDM2) locating in chromosome 12q15 encodes a nuclear-localized E3 ubiquitin ligase.…”
Section: Introductionmentioning
confidence: 99%
“…In year 2018, there were approximately 307 000 new cases of esophageal cancer and 283 000 deaths in China, ranking fifth in the incidence of malignant tumors and fourth in the mortality rate . As is already known, the development of esophageal cancer is the result of the interaction of genes and environmental factors, but the specific pathogenesis of both have not as yet been fully elucidated, and need further exploration . In recent years, studies have confirmed that gene single nucleotide polymorphism (SNP) was closely correlated with the cancer susceptibility …”
Section: Introductionmentioning
confidence: 99%